IMPLEMENTASI PENDIDIKAN AKHLAK PADA ERA MODERN DI MADRASAH IBTIDAIYAH NEGERI 2 BATAM - Badrul Muslim; Isrul Rayu Saputra; Muhammad Ikramul Mutiah; Mar’atus Sholihah; Silvina Sri Aryani; Sangkot Abdullah Efendi Harahap6 (STKIP Subang, 2025)
The development of digital technology and the flow of globalization have had a significant impact on the character formation of students at the elementary school level. This situation presents a unique challenge for Islamic educational institutions, particularly madrasas, in instilling moral values ​​amidst the massive use of digital media and changes in children's social interaction patterns. This study aims to examine the concept of moral education from an Islamic perspective and its implementation at Madrasah Ibtidaiyah Negeri 2 Batam in the context of the modern era. This study uses a qualitative approach with descriptive methods. Data collection was conducted through observations of the activities of the madrasah principal, teachers, and students. Data were analyzed through the stages of data reduction, data presentation, and concluded with data validity tests using source and technique triangulation. The results of the study indicate that moral education at MIN 2 Batam is implemented in an integrated manner through the integration of values ​​into the curriculum, habituation of worship, strengthening madrasah culture, teacher role models, extracurricular activities, and the wise use of technology. Teachers and parents play a strategic role in supporting the moral development of students. However, they still encounter obstacles such as the negative influence of digital media, limited facilities, and limited learning time. Therefore, ongoing collaboration between madrasas, families, and the community is necessary to strengthen the effective implementation of moral education.